2004
DOI: 10.3201/eid1004.030465
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus, Guadeloupe

Abstract: To determine whether West Nile virus (WNV) had reached the archipelago of Guadeloupe, a serologic study in horses and birds was conducted in 2002. Immunoglobulin (Ig) G, IgM, enzyme-linked immunosorbent assay, and seroneutralization tests identified WNV infection in horses and chickens. Six months later, a high rate of seroconversion was observed in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 8 publications
0
41
1
3
Order By: Relevance
“…These rates are significantly higher than the 4.0% (8 of 200 unvaccinated horses) observed in a previously unpublished study (referred to in Komar and Clark, 2006) in 2004 in Trinidad. It is also higher than the rate reported for horses in Venezuela (4.5%; Bosch et al 2007) and Cuba (9.0%; Pupo et al 2006), but lower than in Mexico (29.5-62.5%;Blitvich et al 2003b;Marlenee et al 2004;Alonso-Padilla et al 2009), Guatemala (42.3%;Morales-Betoulle et al 2006), and Guadeloupe (61.6%; Quirin et al 2004). Komar and associates (Komar et al 2003) suggested that the differences in seroprevalence among locations in South and Central America may be a consequence of the difference in the length of time the virus has been in circulation.…”
Section: Discussioncontrasting
confidence: 41%
“…These rates are significantly higher than the 4.0% (8 of 200 unvaccinated horses) observed in a previously unpublished study (referred to in Komar and Clark, 2006) in 2004 in Trinidad. It is also higher than the rate reported for horses in Venezuela (4.5%; Bosch et al 2007) and Cuba (9.0%; Pupo et al 2006), but lower than in Mexico (29.5-62.5%;Blitvich et al 2003b;Marlenee et al 2004;Alonso-Padilla et al 2009), Guatemala (42.3%;Morales-Betoulle et al 2006), and Guadeloupe (61.6%; Quirin et al 2004). Komar and associates (Komar et al 2003) suggested that the differences in seroprevalence among locations in South and Central America may be a consequence of the difference in the length of time the virus has been in circulation.…”
Section: Discussioncontrasting
confidence: 41%
“…In the case of these viruses, and also some alphaviruses, however, chickens develop reliable and robust viraemias and seroconversions (Maguire & Miles, 1965;Campbell & Hore, 1975;Calisher et al ., 1986;Reisen et al ., 1994;Komar et al ., 2001), which allow the use of chickens in vector competence studies and monitoring programmes for virus activity (Morris et al ., 1994;Komar, 2001;Broom et al ., 2002a;Blackmore et al ., 2003;Reisen et al ., 2004;Quirin et al ., 2004). Contrary to these findings, experimental USUV infection only inconsistently led to viraemia and seroconversion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, WNV is reported to produce no clinical signs after experimental infection of chickens, but neutralizing antibodies are consistently found (Senne et al ., 2000;Langevin et al ., 2001). Thus chickens are used as sentinel species for WNV surveillance programmes in North America and in the Caribbean (Langevin et al ., 2001;Quirin et al ., 2004;Reisen et al ., 2004). The enzootic activity of SLEV and Western equine encepha-lomyelitis virus was also monitored by seroconversions in chicken flocks in California (Reisen et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, WNV has extended its distribution in the Americas throughout the United States and southern Canada and has recently been isolated in Mexico (12). Serological evidence suggests that the virus is now widely distributed throughout Mexico (6,12,21) and also parts of the Caribbean (11,16,34). Since 2002, WNV has been responsible for more than 6,300 cases of human meningitis/encephalitis in the United States that resulted in 633 deaths (data from the CDC website, http://www.cdc.gov /westnile, as of 14 December 2004).…”
mentioning
confidence: 99%